If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying w + 12 = 20 Reorder the terms: 12 + w = 20 Solving 12 + w = 20 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + w = 20 + -12 Combine like terms: 12 + -12 = 0 0 + w = 20 + -12 w = 20 + -12 Combine like terms: 20 + -12 = 8 w = 8 Simplifying w = 8
| (y+3)(y+5)=y(y+11) | | -6=-6(3x+-8) | | 5(-10x-11)+11=-4(x+11) | | j+5=96 | | 6x+4=4x+15 | | 72+4y=24 | | 9.85=g-2.15 | | -4+x=-0.5x+5 | | 5x=9x-28 | | 0.86-0.67=0.11x+3.08 | | t-3.84=1.46 | | v+1=10 | | x(x+3)=x+4(x-3) | | n+6.28=19.28 | | 0.545n=n-1 | | g-9=5.75 | | 2j=7.4 | | f-11=1.94 | | 5x+43=10x-17 | | X^2+3x(-2-3)=45 | | -5(70+15-10x+7)=10x | | 4x+4=64-2x | | -4y=6 | | 7+2z=19 | | 5x+13=73-5x | | 3d+2=29 | | 3079.6052=149.4954*h | | 6n^2+n=12 | | -2y=-0.5+3(7y+4) | | 4.50h+2.00=20.00 | | 4x^2+16x-19=6-4x-x^2 | | 4+11+3+11+1*0+1= |